Strength Predicting Model for Foamed Concrete Produced with Rice Husk Ash as Partial Cement Replacement - Agboola Shamsudeen Abdulazeez; Shabi Moshood Olawale; Aliyu Zakari; Musa Abdulhakeem Kolawole; Ridwan Abdulsalam Abiodun; Bukar Aliyu (Journal of Engineering)
Foamed concrete (FC) is a lightweight concrete that can be designed to meet specific strength or density criteria. Foamed concrete with an efficient design, guarantees the desired qualities of durability and strength to be attained. This study aims to predict the compressive strength of foamed concrete produced with rice hush ash as cement partial replacement at 5-30%, using the strength-porosity prediction model with a density of 1600 kg/m3. In order to create the model, a relationship between strength and porosity characteristics was used. The fundamental constant was also found using the numerical analysis bisection method. The characteristics of the fundamental component materials and density that influence the hardened state are examined in this study to investigate the characteristics of foamed concrete. Based on the validity of the results, it can be deduced that the model is appropriate for a laboratory-tested sample of foamed concrete made using rice husk ash as partial cement replacement. Strength-porosity model correlates well with the laboratory-measured strength as it employs the composition of constituents. It is however clear that a strength prediction model can be produced through a selection of criteria such as density, material characteristic properties and proportions to suit different purposes of use and application.